Enterprises (companies) and their associations – subjects of anticompetitive practices - Ovidiu Horia Maican (Juridical Tribune, 2019)
The competition rules applicable to enterprises (companies) are the most important rules of European Union competition law. They have a direct effect and are primarily applicable to companies. Prohibition of agreements restricting competition, abusive exploitation of dominant positions, control of concentrations and state aid are the pillars of European Union competition law.